Protective effect of Trans-resveratrol on Dexamethasone-induced changes in Matrix Metalloproteinases Expression by Human Trabecular Meshwork Cells: potential mechanisms / Normie Aida Mohd Nasir - Mohd Nasir, Normie Aida (2019)
Matrix metalloproteinases (MMPs) can regulate extracellular matrix (ECM) turnover in the trabecular meshwork (TM) of eye. Reduced MMP secretion increases ECM deposition in TM, which is associated with increased intraocular pressure (IOP). Increased IOP is the major risk factor for glaucoma, the leading cause of irreversible blindness, worldwide. Previously trans-resveratrol was shown to reduce IOP in normotensive and oculohypertensive rats. The dose- and time-dependent effects of trans-resveratrol on human TM cells (HTMCs) viability, MMP-2 and -9 secretion and the mechanisms involved remain unknown and hence these effects were investigated in the present study. HTMCs were cultured and divided into 11 groups that received treatment with DMSO (0.1%), dexamethasone (100 nM), and trans-resveratrol (3.125, 6.25, 12.5, 25 and 50 µM) either in the presence or absence of dexamethasone for 2, 5 and 7 days. To study the role of A₁ adenosine receptors (A₁AR) and nuclear factor kappa B (NFĸB) in trans-resveratrol mediated effects on MMP secretions, additional groups of HTMCs were pre-treated with dipropylcyclopentylxanthine (DPCPX), a specific A₁AR antagonist and curcumin, an inhibitor of NFĸB. Cell viability was determined by using MTS assay while MMP-2 and -9 expressions were investigated using western blot. A₁AR expression was determined using western blot and ELISA while NFĸB activation was determined using immunocytochemistry and ELISA. This study demonstrated that incubation of HTMCs with trans-resveratrol up to a concentration of 25 μM does not affect the viability but at 50 µM, it significantly reduces viability of HTMCs both in the presence and absence of dexamethasone. This effect of trans-resveratrol on the viability of HTMCs was dose-dependent but not time-dependent. Dexamethasone reduced MMP-2 and -9 expressions after 5 and 7 days treatment, compared to untreated group (p<0.01). Incubation with 12.5 µM trans-resveratrol for 5 days in the presence of dexamethasone increased MMP-2 and 9 level compared to dexamethasone-treated group (p<0.05). Significant reduction of A₁AR expression was seen in dexamethasone-treated group compared to untreated group (p<0.01). Trans-resveratrol significantly increased A₁AR expression compared to dexamethasone treated and DPCPX-treated groups (p<0.001). Dexamethasone significantly reduced NFĸB activation compared to the untreated group (p<0.001). Increased nuclear localization of phospho p65 NFĸB was seen in trans-resveratrol treated group in the presence and absence of dexamethasone. In conclusion, transresveratrol counteracts the effects of dexamethasone on MMP-2 and -9 levels of HTMCs, which could be mediated by A₁AR and NFĸB.